Adaptation of temperate climate horticultural plants in tropical and subtropical developing countries II. General characteristics, Hungarian experiences and possibilities - Fári, M. G.; Nyéki, J. (International Journal of Horticultural Science, 2001)
The cooperation of Hungarian professionals with Chinese, Thai, South-Korean, Taiwanese and Brazilian colleagues should deserve much more attention than actually done. We refer to the transfer and adaptation of production technologies as well as biotechnological developments in vegetables, fruits, ornamentals and medicinal plants from the Temperate Zone to the tropical and subtropical regions. According to our information Hungarian colleagues involved in extension work are highly esteemed on the same level as Japanese, Chilean, Italian and French colleagues. We could state that immigration of investors, local enterpreneurs as well as those coming from expansive regions of Europe, North America and oversses, representaives of supermakets keeps to be accelerated by the increasing confidence triggered also by the successful management of profitable plantations, vineyards and fruits initiated first about 15 years ago.For Hungary, the presence and achievements of Hungarian horticultural expertise in tropical and subtropical zones yielded unequivocal advantages. Therefore, the next actual step of development would mean the organisation of a network of the "Units of Horticultural Mission" in the tropic and subtropic countries. We are convinced that those Units will stimulate the traffic of technologies as centers of transfer within and between the regions and contribute to the increasing influence of professionals on the production and trade of horticultural commodities. The introduction and testing of new varieties of vegetables, fruits, medicinal plants (as well as ornamentals), the development of the growing technologies, adaptation and acclimation of Temperate Zone germ plasm representing the general trends of advanced production will be the most important tasks of the Mission with a sufficient oversight upon the whole world. It is taken as a fact that Hungarian horticulture and breeding is competitive on the world market. We are ready to contribute to the development of horticulture on a worldwide scale. The Hungarian R & D will be attentive in the future to manage the accumulated capacities by information and mediating needs and offers to the volonteers of the profession. The reality of the above propositions are amply proved by successes of the Agroinvest Co and of other professionals registered in abroad.To keep on the top of the world list of the profession we have to follow up the international trends by our permanent presence on the most important centers of administration and production of the world in order to hold on the hot line of the Hungarian administration competent in financing the R & D activities. We need specialists which are open minded, speak languages, familiar with the tricks of informatics, economics and politics, competent in deals, able to make decisions, etc. The education and training should be strenghtened to he conform with those trends. That proposal involves also the need to follow up the activities of the transnational companies, the regular, active participation on international conferences, the permanent attention paid to electronic informations available in the worldwide networks as well as the printed periodicals of horticulture. It is also related to the attraction of investors to the developments aimed within the country as well as abroad. At last but not at least we have to keep in mind that the work performed abroad by the Hungarian professional is a kind of "para-diplomatic mission" which cannot be substituted by any other, sometimes very expensive activity charged on the officia erliplomatic missions. The benefit of it is, however, valid to the whole country because false stereotypes developed during the last 50 years cannot be abolished otherwise.